Peningkatan Unsur Hara Fospor Tanah Ultisol Melalui Pemberian Pupuk Kandang, Kompos dan Pelet - Yafet Hendri Pasang; Muh. Jayadi; Risma Neswati (Jurnal Ecosolum, 2019)
Ultisol soil has high potential for the development of dryland agriculture. However, this soil use faces obstacles because the nutrient content in Ultisol soils is generally low. This study aims to determine the effect of manure and straw compost on increasing nutrient content of phosphorus in ultisol soil. This study used a completely randomized design (CRD) with 9 levels of treatment, namely P0 = control, P1 = manure 10 tons / ha, P2 = manure 5 tons / ha, P3 = compost 5 tons / ha, P4 = compost 10 ton / ha, P5 = manure 5 tons / ha + compost 10 tons / ha, P6 = manure 10 tons / ha + compost 5 tons / ha, P7 = pellet compost 5 tons / ha, P8 = compost pellets of 10 tons / ha. The treatment was repeated 3 times. The results showed that giving 10 tons / ha of manure plus 5 tons / ha of compost had a significant effect on reducing Al-dd content, and increasing P-available, pH, base saturation, cation exchange capacity and C-organicon Ultisol soil. Giving pellet fertilizer 10 tons / ha gives a real influence on the growth of maize plants.